A mechanism for spin electron acoustic soliton observed in a spin-polarized nanosized electron-hole plasma. (30th December 2021) - Afify, M S; Iqbal, Z; Murtza, G
Abstract: The formation and the characteristics of spin electron acoustic (SEA) soliton in a beam interacting spin-polarized electron-hole plasma are investigated. These wavepackets are supposed to be the source of heating during the excitation process. We have used the separate spin evolution-quantum hydrodynamic (SSE-QHD) model along with Maxwell equations and derived the Korteweg–de Vries (KdV) equation by using the reductive perturbation method (RPM). We note that the larger values of beam density and spin polarization can change the soliton nature from rarefactive to compressive. Our findings may be important to understand the characteristics of localized spin-dependent nonlinear waves in nanosized semiconductor devices.